THE INFLUENCE OF RETURN ON EQUITY AND EARNING PER SHARE ON SHARE PRICES AT PT. BANK CENTRAL ASIA, TBK FOR THE 2013-2022 PERIOD - Adji Widodo; Mainanda Sabrina (Sean Institute, 2023)
This research examines the influence of Return On Equity (ROE) and Earning Per Share (EPS) on share prices at PT Bank Central Asia Tbk during 2013-2022. The research method used is a quantitative method with data analysis using classical assumption tests, simple and multiple linear regression, coefficient of determination tests, and hypothesis testing using SPSS version 25 software. The research results show that ROE does not have a significant influence on share prices partially. Meanwhile, EPS has a partial positive and significant influence on share prices. Simultaneously, ROE and EPS have a positive and significant influence on share prices. This research provides important insights for shareholders and investors interested in analyzing the factors influencing a company's share price.